Neuroprotective Effect of Low-Intensity Transcranial Ultrasound Stimulation in Moderate Traumatic Brain Injury Rats - Zheng, Tao; Du, Juan; Yuan, Yi; Wu, Shuo; Jin, Yinglan; Wang, Zhanqiu; Liu, Defeng; Shi, Qinglei; Wang, Xiaohan; Liu, Lanxiang (Frontiers in Neuroscience, 2020)
Background: Traumatic brain injury (TBI) is a kind of severe brain injury characterized with a high incidence rate and a high disability rate. Low-intensity transcranial ultrasound stimulation (LITUS), as a neuroprotective method can significantly improve the functional prognosis of TBI. Fractional anisotropy (FA) value and mean diffusivity (MD) value can be sensitive to abnormal brain structure and function, and can be used to evaluate the effect of LITUS on TBI. Purpose: To evaluate therapeutic effect of LITUS in moderate TBI rat model with FA and MD values. Methods: Forty-five male Sprague Dawley rats (fifteen sham normal, fifteen TBI and fifteen LITUS treatment rats). Single-shot spin echo echo-planar imaging sequences at 3.0T to obtain DTI parameters. Parameters of FA and MD on the treated side of the injury cortex were measured to evaluate the therapeutic effect of LITUS in a TBI rat model. For FA and MD values, groups were compared using a two-way analysis of variance for repeated measures, followed by Tukey’s post hoc test. Differences were considered significant at P < 0.05. Results: The FA value in the LITUS treatment group at 1 day after TBI was significantly higher than that in the control group (adjusted P=0.0422), and were significantly lower than that in the TBI group at days 14, 21 and 35 days after TBI (adjusted P=0.0015, 0.0064 and 0.0173, respectively). At the end of the scan time point, the differences between the two groups were not significant (adjusted P=0.3242).The MD value in the LITUS treatment group were significantly higher in the early stage than that in the TBI group (adjusted P=0.0167) and significantly lower at the following time points than in the TBI group. Conclusion: Treatment with LITUS by 5min daily effectively improve the brain damage in Controlled Cortical Impact (CCI) caused TBI model. FA and MD value can be served as evaluation indicators for the neuro-protective effect of LITUS.